Crystallographic, Morphological and Optical Properties of Zn1-xCoxS Nanocrystals - Sharma, Kewal Kumar (Asian Journal of Chemistry, 2018)
Cobalt doped zinc sulphide nanocrystals were prepared by co-precipitation route at room temperature. The structural, morphological and optical properties of prepared samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and UV-visible spectroscopy. From XRD patterns, Zn1-xCoxS samples have cubic crystal structure with single in phase. The lattice constant and volume of unit cell were increased with increasing cobalt doping. The crystallite size of prepared samples was in the range of 4-7 nm. The surface morphology of prepared samples was characterized by using transmission electron microscopy. The pure and cobalt doped ZnS samples have spherical like structure. The dislocation density and strain was decreased with increasing cobalt doping. The energy band gap of pure ZnS sample was higher as compared to the cobalt doping, indicated cobalt substitution in ZnS host matrix. Based on this study, the prepared samples have useful in opto-electronics devices and solar cell.